2022
DOI: 10.1007/s00405-022-07798-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between potential risk factors and chronic rhinosinusitis: a bidirectional two-sample Mendelian randomization study

Abstract: Purpose Smoking, alcohol consumption, allergic rhinitis (AR), asthma, and obesity are associated with chronic rhinosinusitis (CRS), albeit the causal relationships between them remain elusive. Therefore, we conducted a bidirectional two-sample Mendelian randomization (MR) study to investigate the bidirectional causal effects between these potential risk factors and CRS. Methods The data for daily cigarette consumption, age of smoking initiation, weekly alcohol consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Interestingly, in contrast to numerous observational studies and a prior MR inquiry 15,36,37 , our research discovered no evidence supporting an association between BMI and CRS. Observational studies often grapple with confounding factors and may encounter issues of reverse causality.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in contrast to numerous observational studies and a prior MR inquiry 15,36,37 , our research discovered no evidence supporting an association between BMI and CRS. Observational studies often grapple with confounding factors and may encounter issues of reverse causality.…”
Section: Discussioncontrasting
confidence: 99%
“…Several observational studies have consistently highlighted connections between AR, asthma, and CRS 7,34 . Moreover, a prior MR study has rmly established a causal link among these conditions 15 . Our ndings align with this conclusion, as we have replicated it using the latest CRS data from FinnGen R10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR falls between interventional epidemiology and observational epidemiology in terms of the hierarchy of evidence ( 32 ). However, there have already been some MR studies on the associations between respiratory illnesses and obesity ( 20 22 , 33 ). There are at least two limitations in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have found that an increase in BMI is associated with an increased risk of pulmonary embolism ( 17 ) and a reduced risk of COPD ( 18 ). There have previously been several Mendelian randomization (MR) analyses that focus on the association between body mass index and respiratory conditions including asthma ( 19 ), COPD ( 20 ), pneumonia ( 21 ), and chronic rhinosinusitis ( 22 ). On the one hand, their study was limited to employing BMI as the only indicator of obesity and did not evaluate the impact of body fat distributions.…”
Section: Introductionmentioning
confidence: 99%